Understanding the factors influencing millennials' clothing brand preference - Huang, Ing (2020)
The research is about understanding the main factors that influence millennials’ clothing brand preference. Consumers of different generation have their own perceptions which impact their brand preference. So, the problem statement of this research is it is important to gain understanding and determine the factors that impact millennials’ clothing brand preference. One of the specific research objectives developed is to find the relationship between emotion and brand preference. It is also carried out to examine the relationship between price and brand preference. It is to find the relationship between self-congruity and brand preference. It is also done to investigate the relationship between brand website and brand preference. Another interesting objective is to determine the role of self-congruity as a mediator between emotion and millennials’ brand preference on clothing. The significance of the study is to have insight into the factors that impact millennials’ clothing brand preference. It is examined through a quantitative research in which online survey is conducted in Malaysia. The target respondents for the survey are millennials which are referring to people born between the years of 1981 and 1996. For the purpose of study, 200 questionnaires are distributed online to respondents who are aged between 23 years old and 38 years old in Malaysia. SPSS is applied to analyse the data collected for this research. The findings show that emotion, price, self-congruity and brand website have significant relationships with brand preference. The study validates a new model which forms the body of knowledge in terms of emotion, price, self-congruity and brand website. The results give practical use to raise the awareness of clothing brands regarding the importance of understanding millennials’ brand preference in order to improve business performance.